A case of hyperprogressive disease following atezolizumab therapy for pulmonary pleomorphic carcinoma with epidermal growth factor receptor mutation. (2021) - Oguri, Tomoyo; Sasada, Shinji; Seki, Sachiko; Murata, Saori; Tsuchiya, Yumi; Ishioka, Kota; Takahashi, Saeko; Seki, Reishi; Hirose, Shigemichi; Katayama, Ryohei; Nakamura, Morio
Abstract: A 66-year old man with non-smoking history was diagnosed with pulmonary pleomorphic carcinoma of the right lower lobe. The carcinoma metastasized to the brain, lungs, pleura, and mediastinal lymph nodes. It was positive for epidermal growth factor receptor (EGFR ) L858R mutation, and tumor cells highly expressed programmed death-ligand 1(PD-L1). Atezolizumab was initiated as the fourth treatment. After three days, he developed cardiac tamponade and immediately underwent pericardial drainage. Computed tomography showed bilateral ground-glass opacity (GGO), significant worsening of multiple lung metastases, and increased size of metastatic lesions. Newly developed metastasis was noted in the lung, and the patient's respiratory condition rapidly deteriorated. He died of respiratory failure on day 13 after atezolizumab administration. The autopsy showed widespread metastasis in all lobes of the bilateral lungs, cardiac tamponade due to carcinomatous pericarditis, carcinomatous lymphangiopathy, and multiple lung metastases, which were thought to be comprehensively the cause of death. These symptoms suggested hyperprogressive disease (HPD). Hence, we report the first case of HPD following atezolizumab therapy for pulmonary pleomorphic carcinoma with EGFR mutation.